O conto brasileiro na 49ª. edição do Prémio Jabuti - Marchezan, Luiz Gonzaga (2008)
Based on the awarding of the 2007 Jabuti Prize for short stories, this paper surveys the trends in contemporary Brazilian short fiction. The Jabuti Prize is the most prestigious literary award in Brazil. Artur Oscar Lopes and João Anzanello Carrascoza were the winners and Autran Dourado, Charles Kiefer, Manalton Braff Rubens Figueiredo and Rubem Fonseca were the shortlisted authors.